(untitled) - Pussa, Tõnu (Boca Raton, 2008)
Combining theory and applications with examples of food-related poisons and poisonings from around the world, Püssa (food toxicology, Estonian University of Life Sciences, Estonia) introduces general and food-specific principles of toxicology at the molecular, cellular, and organism level, emphasizing the biochemical mechanisms of toxic effects. After material on principles, chapters characterize the most important food-borne toxicants, such as endogenous plant toxins, pollutants, mycotoxins, food additives, and veterinary drugs and feed additives. Other areas covered include routes of xenobiotics in an organism, evaluation of the toxicity of substances, and toxicological safety and risk analysis. The book will be of interest to students of food science and technology, professional food scientists, manufacturers, and regulatory agency personnel.
Keywords: Food,Food,Food Contamination,Thực phẩm độc; Toxicology,Toxicity